Evidence that Platelets May Continue to Circulate after Phagocytosis of Particles - Vegge, T; Monn, E; Hjort, P. F (Thrombosis and Haemostasis, 1968)
A suspension of thorium dioxide particles was injected intravenously into rabbits, and platelets were subsequently isolated from the peripheral blood for electron microscopical studies at intervals up to 48 hrs.The injection provoked severe thrombocytopenia. Large numbers of particles adhered to the surface of circulating platelets, and many particles were phagocytosed, probably by invagination of the membrane. Gradually, the load of particles per platelet decreased, and the particles moved into the dense granules of the platelets.We conclude that phagocytosis is not necessarily a lethal event, and platelets may continue to circulate with a heavy load of particles.